Online Impulse Buying in the Youth Context: Hedonic Motives, Emotional Responses, and Involvement in Fashion as Antecedents - Susanto, Prayataneswara Dwiputri (Journal of Business, Management, and Social Studies, 2022)
The main aim of this study is to examine how hedonic motives, emotional variables, and involvement in fashion can impact impulsive behaviors in the fashion industry within Generation Z. The data was collected from 40 respondents through an online survey, with mostly high school graduates located in Jakarta were tested and finally analyzed. The result shows that both hedonic motives and involvement in fashion have significant effects towards impulse buying. However, the research shows that emotional variables did not have a significant impact on impulse buying. The suggested study will contribute to the growing body of online impulse buying knowledge in the context of the youth in a developing country.